A new species of gobiid fish Lentipes niasensis (Gobiidae: Sicydiinae) from Nias Island, Indonesia - Harefa, Tonisman; Chen, I-Shiung (Zootaxa, 2022)
A new species of goby of the subfamily Sicydiinae, Lentipes niasensis, is described from the stream of Humogo River, Nias Island, Indonesia. This species can be distinguished from all congeners by the following combination of features: (1) fin ray counts: D2 I/10; A I/10; P 17–18; D1 not connected to D2 in either sex. (2) squamation: LR 7–11; anterior half of body naked, lateral body scales present from 5–6th rays of second dorsal-fin to hypural, embedded in skin. (3) upper jaw teeth in male 14–19 and in female 33–38. (4) urogenital papilla in male slender and distally pointed, flanked by pair of associated fleshy lobes and not retractable into sheath–like groove. (5) distinctive colour pattern of male: upper lip greyish, red patches on the pectoral-fin base, on mid-body below origin of second dorsal-fin and at caudal peduncle.